Monitoring of particulate matter 10 µm (PM10) in ambient air by means of Gent Sampler as an alternative to Beta Ray Automatic Analyzer for Air Pollution Mitigation - Rina Aprishanty; Rita Mukhtar; Ridwan Fauzi; Dwiana Lestiani; Muhayatun Santoso (Jurnal Ecolab, 2019)
The monitoring of Particulate Matter 10 Mikron (PM10), as one of the critical parameters of air quality in Indonesia, requires equipment that can monitor the actual concentration for 24-hours continuously. Based on that, the anticipation of mitigation against conditions before an episode of pollution occurred can be carried out especially for areas with a history of forest and land fires. This study aimed to find out the correlation between PM10 using Gent sampler and PM10 using Beta Ray Analyzer. It is important to anticipate the current condition of local capacity in fulfilling monitoring data in one area lacking of sophisticated automatic monitoring instrument like Beta Ray Analyzer. The study was conducted at Pekanbaru station which belongs to the regional environmental office in Riau Province, during January 2013 to March 2014 covering 52 available data from manual sampling 24-hour weekly period using Gent Sampler. It was found that the PM10 concentration ranges from 12.7µg/NM3-148.6µg/NM3. The statistical analysis of this preliminary study pertaining the correlation coefficient of the two instruments reading is as high as 0.803. Pearson correlation analysis was employed in drawing the statistical inference. It is of interest to conclude that the gravimetric method of Gent Sampler can be used as an alternative method in monitoring particulate in ambient air.